Awareness and Perception of Urinary Tract Infections among Women in South India: A Cross-Sectional KAP Study - Muppa, Leena; Udayakumaran, Narmadha; Thiyagarajan, Balaji; Balaji, Madhumitha; Arumugam, Lavanya (Indian Journal of Pharmacy Practice)
Background: Urinary Tract Infections (UTIs) are among the most common bacterial infections affecting women worldwide, often leading to serious complications if not managed appropriately. Aim and Objectives: To evaluate the Knowledge, Attitudes, and Practices (KAP) related to UTIs among women in South India, with a focus on identifying awareness levels and behavioural patterns that influence prevention and management. Materials and Methods: A cross-sectional survey was conducted among 250 female participants, assessing their understanding of UTI causes, symptoms, treatment approaches, and hygiene practices. Results: Findings revealed that while a moderate level of awareness existed, less than half of the respondents could correctly identify bacteria as the primary cause of UTIs. Although most participants demonstrated positive attitudes toward seeking medical attention and maintaining hydration, gaps in knowledge about preventive measures and transmission persisted. Younger women (aged 15-25) displayed significantly higher knowledge and more favourable attitudes compared to older age groups. Hygienic practices, such as proper menstrual hygiene and drying undergarments in sunlight, were commonly observed, though misconceptions and social stigma limited open discussions in some cases. Conclusion: The study underscores the need for targeted health education programs, improved sanitation infrastructure, and open dialogue to bridge knowledge gaps and enhance preventive behaviours related to UTIs in women.
Keywords: Urinary Tract Infections; KAP; Women’s Health; South India; Hygiene; Menstrual Hygiene